Inferências filogenéticas de cinco estirpes isoladas de Leptospira de suínos baseados nos genes 16s e secY - Bastos, C. R.; Marulanda, N. D. F.; Jaeger, L. H.; Miranda, V. F. O.; Lilenbaum, W.; Mathias, L. A. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is a zoonosis responsiblefor economic and health damages in swine herds. Thecultivation and typing of leptospira strains present in oneregion are still an important subject for disease control.